The Composition of The Catch in The Danish Seine Operating in The Java Sea - Simanullang, Rio Prasetyo; Suharyanto, Suharyanto; Perangin-angin, Robet (Politeknik Kelautan dan Perikanan Karawang, 2023)
Fishing gear with a good level of environmental friendliness will be selective in fishing, by choosing the right location and using net mesh sizes that can select the fish to be caught. For this reason, this study was carried out to analyze the composition of the catch from the Pocket Drag Net. The types of fish caught in percentage are as follows: swanggi fish (Priacanthus tayenus) at 29.9%; etong fish (Abalistes stellaris) by 11.2%; mackerel (Scomberomorus commerson) by 0.14%; tiger grouper (Epinephelus fuscoguttatus) by 1.5%; yellowtail fish (Caesio teres) by 1.7%; red snapper (Lutjanus sp.) by 0.7%; Stingray (Dasiatis zugei) at 1.5%; Kurisi fish (Nemipterus japonicus) amounted to 22.2%; Ray shark (Rhynchobatus australiae) by 1.15%; Brown (Scolopsis taeniopterus) by 21.2%; and Manyung (Netuma thalassina) at 7.9%. Based on the percentage composition of the catch, Swanggi fish is the highest main catch fish with a percentage of 29.9% and the lowest main catch fish is red snapper, namely 0.7%. Meanwhile, by-catch fish such as mackerel were also caught with a percentage of 0.14%.